(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2022)
Drug addiction has significantly increased in the whole world, especially in the South Asian countries like Bangladesh. In this country, this agent of human devastation has spread its tentacles to every nook and corner. International organizations like the United Nations and World Health Organization (WHO) are alarmed by the present proportion of addicts. Including information on drug usage, it is much more a time honored issue to understand or acquire new concept about drug abuse. Many people don’t understand why or how other people become addicted to drugs. They may mistakenly think that those who use drugs lack moral principles or willpower and that they could stop their drug use simply by choosing to. In reality, drug addiction is a complex disease, and quitting usually takes more than good intentions or a strong will. Drugs change the brain in ways that make quitting hard, even for those who want to. Fortunately, researchers know more than ever about how drugs affect the brain and have found treatments that can help people recover from drug addiction and lead productive lives. Journal of National Institute of Neurosciences Bangladesh, January 2022; 8(1):84-89